REDEFINISI DIAGNOSTIK DALAM KONSELING (Sebuah Isu Profesi Konseling) - Suwarjo Suwarjo (Paradigma, 2009)
Diagnostic as one of the strides in counseling has been such a great polemic for a long time. One of the activities in diagnostic is classifying the diseases and planning their treatments (in the beginning, it is applied in clinical setting). It can’t merely be applied in counseling for normal persons. That in one of the causes of appearing the controversy about the function of diagnostic in counseling. This paper attains to investigate deeply about something which relate to various arguments between the pros and contras toward the diagnostic activities in counseling. At the end of the investigation in this paper, it states the important of the redefinition of diagnostic in counseling. Therefore, the diagnostic can also cover various activities to find out some positive aspect from the clients that can be developed optimally (developmental diagnostic).Keywords : Diagnostic, psychological diagnostic.